Robotic Process Automation: Peran dan Tantangan Akuntan Indonesia di Masa depan - RAMARDHAN, FRIZKA PUTRI (Jurnal Ilmiah Mahasiswa FEB, 2018)
Robotic Process Automation (RPA) is a form of technology that combines artificial intelligence and human intelligence. Indrustrial Revolution 4.0 triggers the emergece of RPA in accounting. The objective of this  research  is  to  study  the  effect  of  RPA  emergence  on  Indonesia accountant profession in the future. The data of the qualitative descriptive research are primary data abtained from interviews with accounting practioners and lectures.  This research concludes that RPA will not be replace the position of accountant. The role of accountants un the future will be as tax consultants, financial analysts, financial planner, and public accountant. Special skills they need are taxes, financial statement analysis, certificated of profesional skill, and communication. Keyword:   Robotic   Process   Automation,   Indrustrial   Revolution   4.0, accountant role, ability, triangulation